Integrating Sustainability Reporting into Management Accounting: A Pathway to Enhanced Corporate Governance - Purwandaningsih, Sintya; Ristanto, Ristanto; Lase, Luther Hasan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The integration of sustainability reporting into management accounting has become a crucial pathway for advancing corporate governance in an era increasingly driven by environmental, social, and governance (ESG) considerations. Traditional management accounting primarily focused on financial efficiency and performance measurement; however, contemporary corporate practices demand a broader framework that captures both financial and non-financial dimensions of organizational value creation. This study examines the role of sustainability reporting as a complementary mechanism within management accounting systems to strengthen transparency, accountability, and long-term decision-making. By embedding sustainability indicators—such as carbon emissions, resource efficiency, social responsibility, and ethical governance—into accounting processes, firms can provide stakeholders with a more holistic representation of corporate performance. The findings highlight that companies integrating sustainability metrics into management accounting not only enhance the reliability of their internal control systems but also improve stakeholder trust, regulatory compliance, and risk management. Furthermore, the study underscores that this integration supports board-level governance by aligning corporate strategies with sustainable development goals (SDGs) and fostering responsible investment practices. Methodologically, the analysis is grounded in a review of empirical research and best practices across developed and emerging economies, demonstrating that sustainability-oriented management accounting can act as a bridge between financial reporting and corporate governance mechanisms. In conclusion, the integration of sustainability reporting into management accounting contributes to building resilient, ethically governed organizations capable of achieving long-term competitiveness while meeting societal expectations.